Method of structural synthesis of the power supply network of critical infrastructure facilities - Shvorov, S.; Opryshko, O.; Polishchuk, R.; Ivashchuk, V. (Energy and Automation, 2025)
At present, the urgent problem is to enhance the structural resilience of energy networks against their constant destruction caused by air attacks. The article examines the issue of integrating decentralized generation sources to ensure the energy autonomy of critical infrastructure facilities. The purpose of the study is to improve the structural resilience of energy supply networks for critical infrastructure based on the optimal integration of renewable energy sources, biogas plants, and energy storage systems. To achieve this objective, the problem statement was formulated, and a modified branch and bound method was proposed for its solution. An algorithm for solving the multi-criteria optimization problem of energy network structures was developed. The main results confirm that the optimal structural integration of solar and wind generation, biogas plants, and batteries makes it possible to cover critical loads under forecasted conditions. The implementation of such systems significantly increases the structural resilience of energy systems and creates conditions for the sustainable development of energy-independent communities.Key words: structural stability, power grid, solar, wind generation, energy storage, biogas plants, optimization